On TADs and LADs: Spatial Control Over Gene Expression. Issue 8 (August 2016) - Gonzalez-Sandoval, Adriana; Gasser, Susan M.
Abstract : The combinatorial action of transcription factors drives cell-type-specific gene expression patterns. However, transcription factor binding and gene regulation occur in the context of chromatin, which modulates DNA accessibility. High-resolution chromatin interaction maps have defined units of chromatin that are in spatial proximity, called topologically associated domains (TADs). TADs can be further classified based on expression activity, replication timing, or the histone marks or non-histone proteins associated with them. Independently, other chromatin domains have been defined by their likelihood to interact with non-DNA structures, such as the nuclear lamina. Lamina-associated domains (LADs) correlate with low gene expression and late replication timing. TADs and LADs have recently been evaluated with respect to cell-type-specific gene expression. The results shed light on the relevance of these forms of chromatin organization for transcriptional regulation, and address specifically how chromatin sequestration influences cell fate decisions during organismal development. Trends: Novel techniques have identified subdomains of chromatin defined by the likelihood of DNA–DNA contacts within a contiguous domain, called TADs. Chromatin distribution with respect to the nuclear lamina can be mapped by tagging DNA that contacts nuclear envelope components, called LADs. During development, the spatial organization of genes within the nucleus changes with cell fate decisions, showing changes in both types of organization. Switching promoter–TAD proximity at the mouse HoxD cluster drives the proper expression of genes within the cluster, while altered EPHA4 TAD boundaries generate limb malformations. The loss of chromatin sequestration at the nuclear lamina impairs the efficiency with which muscle cell induction occurs in worm embryos.